2014
DOI: 10.1088/0004-637x/785/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activity and Oscillation Amplitudes of Red Giants in Eclipsing Binaries

Abstract: Among 19 red-giant stars belonging to eclipsing binary systems that have been identified in Kepler data, 15 display solar-like oscillations. We study whether the absence of mode detection in the remaining 4 is an observational bias or possibly evidence of mode damping that originates from tidal interactions. A careful analysis of the corresponding Kepler light curves shows that modes with amplitudes that are usually observed in red giants would have been detected if they were present. We observe that mode depl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
136
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(151 citation statements)
references
References 30 publications
15
136
0
Order By: Relevance
“…The methods we use are described in Gaulme et al (2013Gaulme et al ( , 2014, and here we provide a summary. The way light curves are processed is of prime importance becausepart of the conclusions of this paper depends on our ability to provide reliable estimates of stellar radii.…”
Section: Kepler Photometric Light Curvesmentioning
confidence: 99%
“…The methods we use are described in Gaulme et al (2013Gaulme et al ( , 2014, and here we provide a summary. The way light curves are processed is of prime importance becausepart of the conclusions of this paper depends on our ability to provide reliable estimates of stellar radii.…”
Section: Kepler Photometric Light Curvesmentioning
confidence: 99%
“…Among dwarfs, comparing asteroseismic radii to radii from Hipparcos parallax and bolometric flux (Silva Aguirre et al 2012) and to radii from interferometry (Huber et al 2012) show agreement to within 5%. RGB radii comparisons show mixed results (see Huber et al 2012;Frandsen et al 2013;Gaulme et al 2014;Brogaard et al 2016;Gaulme et al 2016).…”
Section: Tgas-asteroseismic Parallax Zeropointmentioning
confidence: 99%
“…Despite these challenges, such systems will provide further tests of stellar structure and evolution when they are found, just as systems with a single oscillating red giant have already (e.g. Hekker et al 2010b;Frandsen et al 2013;Gaulme et al 2013Gaulme et al , 2014Beck et al 2014;Rawls et al 2016). With the future missions TESS (Ricker et al 2015;Campante et al 2016) and PLATO (Rauer et al 2014) to provide asteroseismic data for many more systems, there will be good opportunities to find more such asteroseismic binary systems.…”
Section: Discussionmentioning
confidence: 99%
“…Mathur et al 2013), particularly amongst the many red giants that have been observed (e.g. Hekker et al 2010b;Frandsen et al 2013;Gaulme et al 2013Gaulme et al , 2014Beck et al 2014;Rawls et al 2016). In addition, KIC 4471379 (Murphy et al 2014) is a binary in which both components are δ Scuti pulsators, while KIC 10080943 (Schmid et al 2015;Keen et al 2015) has two γ Doradus/δ Scuti hybrids.…”
Section: Introductionmentioning
confidence: 99%